Principles of electronic materials and devices - Kasap, S. O. (Boston, Massachusetts : McGraw Hill Education, 2002)
This textbook presents a first course in electronic materials and devices for undergraduate students. The second edition is an updated and revised version of the first edition based on reviewer comments.
Ch. 1. Elementary Materials Science Concepts -- Ch. 2. Electrical and Thermal Conduction in Solids -- Ch. 3. Elementary Quantum Physics -- Ch. 4. Modern Theory of Solids -- Ch. 5. Semiconductors -- Ch. 6. Semiconductor Devices -- Ch. 7. Dielectric Materials and Insulation -- Ch. 8. Magnetic Properties and Superconductivity -- Ch. 9. Optical Properties of Materials -- App. B. Elements to Uranium.
Includes bibliographical references and index.
Keywords: ELECTRICAL ENGINEERING -- MATERIALS